Laxman Karki’s Story: A Case on Successful Entrepreneurship - Pant, Sushil Kumar (Journal of Nepalese Business Studies, 2006)
No abstract available. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.53-57